Penerapan Media Digital Storytelling Untuk Meningkatkan Keterampilan Menulis Teks Laporan Hasil Observasi - Dian Hasriani Ridwan; Nurhusna; St.Nurhaedah (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2024)
This study aims to describe the learning outcomes of observation report text writing skills by applying digital storytelling media. This type of research is Classroom Action Research. The population in this research is all students of class VIII of SMPN 2 Sungguminasa. Samples in this research were students of class VIII.5 with a total of 30 students consisting of 15 male students and 15 female students. Data collection techniques in this research used observation and assignment bars. The data were analysed qualitatively and quantitatively. The results showed that digital storytelling media can improve the writing skills of students of class VIII.5 SMP Negeri 2 Sungguminasa. The learning outcomes of writing observation report text in cycle I were 11 or 36.7% students who reached the KKM score and as many as 19 or 63.3% students had not reached the KKM score. In cycle II, the results of writing observation report text increased, namely there were 26 or 86.7% students who reached the KKM score and as many as 4 or 13.3% students had not reached the KKM score.